Identifying meaning by contrast or: how to render implicit knowledge explicit - Schwenk, Hans Jörg (Glottodidactica, 2018)
The paper deals with verbal meaning deficiencies caused by lack of explicit knowledge occurring in Polish and German monolingual dictionaries with respect to the morphological categories of aspect and manner of action. The author shows that contrastive analysis has proved to be the chief means of identifying meaning and rendering implicit knowledge explicit, thus giving birth to the concept of horizontal lexicography and its realization.